General physics 1 - Santos, Gil Nonato C. (Sampaloc, Manila : Rex Book Store, Inc., 2017)
"General Physics 1 contains discussions about technology, discoveries, and inventions of scientists and engineers with their respective works in relation to the basic concepts of physics. This book covers the following topics: motion, acceleration, circular motion, momentum, work and energy, gravity, force, wave, sound, fluids, and heat. It was aligned with the Department of Education's K to 12 program for General Physics 1 curriculum under the Science, Technology, Engineering, and Mathematics (STEM) strand for Grade 12 and designed based on the 7Es of learning cycle and instructional model: Elicit, Engage, Explore, Explain, Elaborate, Evaluate and Extend."
Includes references and index.
Keywords: Physics -- Study and teaching